Unraveling the Volcanic Structure of Oceanic Islands—Gravity Survey of Socorro Island, Revillagigedo Archipelago, Mathematician Ridge, Pacific Plate - Pavón‑Moreno, Julio A.; Urrutia‑Fucugauchi, Jaime; Pérez‑Cruz, Ligia; Escorza‑Reyes, Marisol (Earth and Planetary Science, 2026)
Results of a gravity survey of Socorro Island are used to investigate the volcanic structure of an oceanic island in the Mathematician Ridge, Eastern Pacific Ocean. The volcanic activity during the Quaternary is divided into pre-, syn-, and post-caldera stages, associated with a partly preserved caldera characterized by dominant alkali basalts and silicic peralkaline flows and domes. Recent Holocene activity includes basalt flows and cones of the Lomas Coloradas field. Bouguer anomalies correlate with the volcanic structure and topographic features, with low values over the summit caldera, intermediate-wavelength, intermediate-amplitude anomalies over the slope, and high-amplitude anomalies in the Lomas Coloradas. The regional anomaly field shows trends over the Evermann shield volcano, with broad positive anomalies over post-caldera deposits. The residual field shows small-wavelength anomalies over the caldera, caldera rim, slope, and pre- and post-caldera deposits, with isolated positive anomalies over pre-caldera volcanics and younger post-caldera deposits. Upward and downward analytical continuations, along with the first and second vertical derivatives, constrain the anomaly sources. Forward 2.5-D models with different geometries and density contrasts enable analysis of subsurface structure and stratigraphy. Basal sequences for the shield edifice are formed by basaltic and pyroclastic layered sequences. The residual gravity response is associated with units on top of the basal sequence and with post-caldera activity. From the gravity models, we estimate a post-caldera subsidence depth in the range of ~100 m that correlates with an estimated ~2 km3 erupted volume and ~4.5 × 3.8 km caldera. ER